From the field to the lab: Muriqui endocrinology from a collaborative perspective. Issue 5 (30th October 2018) - Strier, Karen B.; Ziegler, Toni E.
Abstract : The northern muriqui ( Brachyteles hypoxanthus ) is a critically endangered species endemic to the Atlantic Forest of southeastern Brazil. Long‐term observational studies of wild muriquis have provided many insights into the behavioral ecology and life history of this species. However, nearly everything that is currently known about the northern muriqui's behavioral endocrinology has come from combining our respective expertise in noninvasive field and laboratory research. Here, we reflect on the history of our collaboration, focusing on major challenges, key scientific findings, and factors that contributed to its success. Challenges included insuring the reliable collection of frequent fecal samples from a large enough number of known individuals over extended periods of time, preserving the steroids in the field and transporting them, developing and validating the fecal steroid assays, and interpreting the hormonal profiles within the behavioral and ecological contexts of the study subjects. Major findings included our thorough description of the fecal progesterone and estradiol profiles associated with muriqui ovarian cycling and gestation, the seasonal resumption of cycling, its onset during puberty of dispersing females, and the differences between fertile and infertile cycles. We also documented the relationship between fecal cortisol and testosterone in sexually active males across breeding and nonbreeding seasons, and sex differences in cortisol levels across the mating and conception seasons. We attribute the success of our collaboration to a number of factors including our mutual appreciation for one another's high standards for ethics, data quality, and data interpretation. Abstract : The authors (Karen Strier and Toni Ziegler) early in the morning at Karen's field site in southeastern Brazil, 18 January 2000.